Simultaneous gastric cancer and breast cancer metastases to the stomach with lymph node collision tumor: a case report - Takeshi Okamoto; Hidekazu Suzuki; Katsuyuki Fukuda (BMC Gastroenterology, 2021)
Abstract Background While double primary cancers are common in breast cancer patients, co-existence of primary gastric cancer and gastric metastases of breast cancer is exceedingly rare. Case presentation A 51-year-old woman receiving chemotherapy for breast cancer presented with melena and presyncope. A circumferential thickening of the pylorus and small submucosal tumor-like lesions in the gastric fundus and corpus were confirmed on endoscopy. Immunohistochemistry of biopsies revealed that the former was composed of poorly differentiated gastric cancer cells, while the latter were breast cancer metastases. Distal gastrectomy was performed. Pathological evaluation of the resected specimen revealed gastric adenocarcinoma in the pyloric lesion and breast countless cancer metastases throughout the remainder of the stomach, with positive margins. One lymph node had evidence of both stomach cancer and breast cancer metastases, forming a collision tumor. Despite a successful surgery, the patient died 6 months later due to progression of breast cancer. Conclusion We report a case of synchronous primary gastric adenocarcinoma and gastric metastases of breast cancer. Inter-disciplinary collaboration is crucial in determining the optimal treatment in double cancers.